Liver transplantation in Central Europe - Trunecka, Pavel; Gerlei, Zsuzsanna; Lisik, Wojciech; Skladany, Lubomir; Fronek, Jiri; Hrusovsky, Stefan; Małkowski, Piotr (Clinical and Experimental Hepatology, 2016)
Introduction: Transplant hepatologists convened in Warsaw on 20-21 November 2015 at a meeting of the Initiative Group for Central European Hepatologic Collaboration to exchange their experience in liver transplantation in their respective countries. Material and methods : The description is based on narration of individual country representatives, supplemented by data from additional queries, and from publicly accessible sources. Results : Liver transplantation programs were launched, in the Czech Republic in 1983, in Poland in 1990 (paediatric) followed by the adult program 1994; the first liver transplant in Hungary was performed in 1995, with Slovakia launching its liver transplantation program in 2008. Currently, there are 2 centres for liver transplantation in Slovakia, 1 centre in Hungary, 6 centres in Poland, and 2 centres in the Czech Republic. The rates of liver transplantation correspond to the number of cadaveric donations being the highest in the Czech Republic (15.8 per million population) and the lowest in Slovakia (4.2 per million population) (2014 data). Live donation is utilized systematically in Poland. Indications vary from country to country, but the 3 most frequent ones include hepatitis C and B cirrhosis, alcoholic cirrhosis, and cholestatic liver disorders. There is a growing incidence of hepatocellular carcinoma among adult liver transplant recipients. Biliary atresia and hereditary diseases are the most frequent indications among children. Hungary became a member of Eurotransplant, other countries are not a part of any international organization for organ sharing. Conclusions : Despite some differences, liver transplant programs seem to be compatible honouring the same values and principles universal to liver transplant programs in most parts of the world.